English Indefinite Aspect: Development in Diachrony and Synchrony - Erzhumanova А.; Elubai А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The category of aspect is one of those that has not yet been resolved in linguistics. English has four categories of aspects: indefinite, continuous, ideal, and ideal continuous. This article discusses the concept of “aspect” in the linguistics of the English language, as well as the meaning and form of the indefinite aspect of the English language in the development of diachrony and synchronism. Based on examples of literary works of different periods, an indefinite aspect existed in the ancient era, and the universality of its use was proved.